Black Men Through Black Women’s Lens: peripheral resistance in the voices of Racionais MC’s through black feminism - de Oliveira Ruas, Maria Fernanda (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2025)
This article proposes a reading of the work of the Racionais MC’s based on the contributions of black feminist authors such as bell hooks (2019; 2022), Audre Lorde (2019), Patricia Hill Collins (2019) and Saidiya Hartman (2022), who offer theoretical and methodological tools for valuing knowledge produced in the margins. The analysis starts from the construction of black subjectivities crossed by racism, discusses rap as an instrument of political empowerment and addresses critical fabrication as a counter-historical practice. Anchored in the documentary “Racionais: Das Ruas de São Paulo pro Mundo” (Racionais MC’s: From the Streets of São Paulo), the reflection highlights how the group articulates narratives that denounce structural violence and affirm possibilities for existence and political awareness among young blacks from the periphery.